2001
DOI: 10.1051/rnd:2001109
|View full text |Cite
|
Sign up to set email alerts
|

In primiparous sows, plasma insulin-like growth factor-I can be affected by lactational feed intake and dietary energy source and is associated with luteinizing hormone

Abstract: -During a 21-day lactation period, 48 primiparous sows were fed a fat-or a starch-rich diet (131 g fat and 183 g starch + sugar . kg -1 vs. 31 g fat and 351 g starch + sugar . kg -1 ) at a high or a low level of feeding (44 vs. 33 MJ net energy per day) according to a factorial design. Blood samples were collected at days 7, 14, 21, 22 (weaning), 24, 25, 26, and 27 post-partum (p.p.). IGF-I levels were higher with the starch-rich than with the fat-rich diet at days 7, 21, 22, and 24 p.p. Plasma IGF-I concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 24 publications
5
47
1
1
Order By: Relevance
“…Indeed in our sows, insulin and IGF-1 concentrations before weaning were negatively related to sow BW loss during lactation, and positively related to sow backfat thickness at weaning, as also observed by Hoving et al (2012) and Rojkittikhun et al (1993). After weaning, sows change towards an anabolic state, associated with restoration of plasma insulin and IGF-1 concentrations (Van den Brand et al, 2001a;Wientjes et al, 2012b). In our sows, after weaning a quick restoration of insulin secretion took place and no relations existed between pre-and postweaning insulin levels.…”
supporting
confidence: 79%
“…Indeed in our sows, insulin and IGF-1 concentrations before weaning were negatively related to sow BW loss during lactation, and positively related to sow backfat thickness at weaning, as also observed by Hoving et al (2012) and Rojkittikhun et al (1993). After weaning, sows change towards an anabolic state, associated with restoration of plasma insulin and IGF-1 concentrations (Van den Brand et al, 2001a;Wientjes et al, 2012b). In our sows, after weaning a quick restoration of insulin secretion took place and no relations existed between pre-and postweaning insulin levels.…”
supporting
confidence: 79%
“…To our understanding, insulin may be a potential mediator of these treatment effects. As mentioned previously, higher insulin levels are positively associated to LH pulsatility in sows (van den Brand et al, 2001), as it might affect the GnRH pulse generator. For instance, van den Brand et al (2000a) and Ziecik et al (2002) reported that dextrose containing feed increased insulin and IGF-1 levels (van den Brand et al, 2001) and follicle size (van den Brand et al, 2000a;Wientjes et al, 2012b).…”
Section: Discussionmentioning
confidence: 62%
“…As mentioned previously, higher insulin levels are positively associated to LH pulsatility in sows (van den Brand et al, 2001), as it might affect the GnRH pulse generator. For instance, van den Brand et al (2000a) and Ziecik et al (2002) reported that dextrose containing feed increased insulin and IGF-1 levels (van den Brand et al, 2001) and follicle size (van den Brand et al, 2000a;Wientjes et al, 2012b). Comparable effects were recently demonstrated by Quesnel et al (2007), as they showed that sows with a high and prolonged insulin response after a glucose tolerance test had more and better developed follicles.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations